PENGARUH KETERAMPILAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA KONVEKSI ISTANA MODE MADIUN - Wiwin Wiranti (Universitas PGRI Madiun, 2016)
This study aims to determine tbe Employee Skills in the Konveksi Istana Mode Madiun, to determine Employee Productivity in the Konveksi Istana Mode Madiun, as well as to determine the presence or absence of Vocational Effect on Productivity Among Employees at the Konveksi Istana Mode Madiun. The samples in this study is purposive sampling technique that all employees at the Konveksi Istana Mode Madiun part of convection, amounting to 30 people. Data collection using questionnaires, documentation and interviews.In analyzing the data using statistical methods Product Moment, To test this hypothesis using the r test, F test and t test. The results of the regression analysis ofY = a +bX, the result Y = 11,737 + 0,757X, to test that rcount > r liable (0.784 > 0.361), or may be rejected HO means that there is a skills significant relationship with work productivity of employee at the Konveksi Istana Mode Madiun. Furthermore, also obtained results which indicate that the F test ofF count >F table (44,5752::4.196) or ::;;Sighit Sigprob (0,000 ::;;0.05). Thus HO is rejected, it means there is an overall effect of skills on labor productivity at the Konveksi Istana Mode Madiun. In addition, the t-test results obtained thit> ttab (6.676 > 2.048) or Sig hit < Sig prob (0.000 < 0.025) this situation can be said to be no different from the effect of employee skills on work productivity of employee at the Konveksi Istana Mode Madiun.